Plasma procalcitonin and C-reactive protein concentrations in dogs with bacterial sepsis and non-infectious systemic inflammatory response syndrome - Rompf, Johanna; Lutz, Bérénice; Adamik, Katja-Nicole; Marti, Eliane; Mirkovitch, Jelena; Peters, Laureen Michèle; Eiermann, Jennifer; Schüpbach-Regula, Gertraud; Hettlich, Bianca; Willi, Barbara; Schuller, Simone (Frontiers in Veterinary Science, 2025)
Procalcitonin is a well-established biomarker of bacterial infections in human medicine, used to guide initiation and duration of antimicrobial treatment. C-reactive protein (CRP) is a frequently used marker of inflammation in dogs, but is not specific for bacterial infection. The main objective of this study was to determine kinetics of plasma PCT (pPCT) and CRP in dogs with sepsis, non-infectious systemic inflammatory response syndrome (nSIRS) and healthy dogs. This prospective, observational study included 17 dogs with sepsis, 16 with nSIRS and 15 healthy dogs. Hematologic parameters, pPCT and CRP were assessed on days 1, 2 and 3 in healthy dogs and on days 1, 2, 3 and 4 in dogs with nSIRS or sepsis. The shortened Acute Patient Physiologic and Laboratory Evaluation (APPLEfast) score was calculated for dogs with sepsis and nSIRS. Plasma PCT was measured using a validated canine PCT ELISA. There was no significant difference in median pPCT between healthy dogs (110.3 pg/mL; IQR 74.7–138) and dogs with sepsis (81.6 pg/mL; IQR 50.1–157.1) or nSIRS (105.3 pg/mL; IQR 87.6–164.7). Prior antimicrobial treatment was not associated with a decrease in pPCT concentration in septic dogs. In the sepsis group, day 1 pPCT concentrations were significantly higher in non-survivors than in survivors (p < 0.05). In contrast, median CRP was above the reference range (<10.5 mg/L) in dogs with nSIRS (100.7 mg/L; IQR 67–141.9) or sepsis (131.9 mg/L; IQR 75.7–194.8) and significantly decreased within the first 4 days of successful antimicrobial treatment of sepsis. In conclusion, while plasma PCT showed some prognostic value, it was not a useful biomarker for assessing the efficacy of the chosen antimicrobial treatment in dogs with sepsis.